Diversity of attacking actions in Malaysian junior and senior taekwondo players - Tan, Y. L.; Krasilshchikov, O. (International Journal of Performance Analysis in Sport, 2015)
Extensive research has been attempted in sports recently by implementing video/notational analysis, given that its benefits in improving performance have been shown to exist. The present study was conducted to determine whether the taekwondo junior and senior athletes differ in: (1) their attacking techniques of choice and (2) opting for various value groups of scoring kicks during taekwondo match. A total of 38 matches of 11 seniors and 10 juniors during a national level taekwondo competition were recorded for the research on the frequency and variety of the techniques attempted in a match through notational analysis. The results revealed significant differences.